Right Here Right Now (RHRN) pilot study: testing a method of near-real-time data collection on the social determinants of health. (1st June 2018) - Naven, Lynn; Inglis, Greig; Harris, Rachel; Fergie, Gillian; Teal, Gemma; Phipps, Rebecca; Stewart, Sally; Kelly, Lorna; Hilton, Shona; Smith, Madeline; McCartney, Gerry; Walsh, David; et al.
Abstract : Background Informing policy and practice with up-to-date evidence on the social determinants of health is an ongoing challenge. One limitation of traditional approaches is the time-lag between identification of a policy or practice need and availability of results. The Right Here Right Now (RHRN) study piloted a near-real-time data-collection process to investigate whether this gap could be bridged.Methods A website was developed to facilitate the issue of questions, data capture and presentation of findings. Respondents were recruited using two distinct methods ‐ a clustered random probability sample, and a quota sample from street stalls. Weekly four-part questions were issued by email, Short Messaging Service (SMS or text) or post. Quantitative data were descriptively summarised, qualitative data thematically analysed, and a summary report circulated two weeks after each question was issued. The pilot spanned 26 weeks.Results It proved possible to recruit and retain a panel of respondents providing quantitative and qualitative data on a range of issues. The samples were subject to similar recruitment and response biases as more traditional data-collection approaches. Participants valued the potential to influence change, and stakeholders were enthusiastic about the findings generated, despite reservations about the lack of sample representativeness. Stakeholders acknowledged that decision-making processes are not flexible enough to respond to weekly evidence.Conclusion RHRN produced a process for collecting near-real-time data for policy-relevant topics, although obtaining and maintaining representative samples was problematic. Adaptations were identified to inform a more sustainable model of near-real-time data collection and dissemination in the future.Key messages RHRN aimed to capture people's everyday experiences to provide timely insights for policy-makers.It proved feasible to run a multi-mode weekly data-collection process to inform decision-makers.Difficulties recruiting a representative sample limited the utility of the quantitative data.Decision-making processes were not flexible enough to respond to rapid weekly evidence generation.